Detection and Diagnosis of Defect in GIS Based on X-ray Digital Imaging Technology - Tianhui Li (Energies, 2020)
For better application of X-ray digital imaging technology in defect detection in Gas Insulated Switchgear (GIS), it is essential to investigate the typical defect and establish the defect database, which has not been adequately performed in previous work. Systematic experimental research is also needed to accumulate data and experience. In this research, an experimental platform, including Computed Radiography (CR) imaging system and a GIS model, is built, and extensive tests of different kinds of typical defects are studied. The influence X-ray irradiation on SF6 under different tube voltage levels is firstly examined, which proves that the withstand voltage of SF6 gas has not been affected and no dissociation has been found. Then, several kinds of defects are tested by X-ray digital imaging technology. The successful application examples of “visual” detection of defects further prove the practicability and validity of the X-ray digital imaging technique. Finally, the image database of typical defects inside of GIS is established and the defect risk is also analyzed in three levels, which would be useful for the defect severity diagnosis and risk assessment.